Analyzing cultural and work related values in Thailand / Jennifer Ann Swanson, Kellyann Berube Kowalski and Matthew H. Roy (Faculty of Business and Management ; UiTM Press, 2005)
This study focuses on work-related values of Thais and their potential effect on multinational operation. In an attempt to increase the success rate of expatriates working in Thailand, the key factors, cultural values and gender roles were studied using the Bern Role Scale. This research confirmed Hofstede s earlier findings that individuals in Thailand score high on the feminine dimension, i.e., a need for affiliation as opposed to the masculine dimension, i.e., a need for achievement. Therefore, the implication to expatriates working in Thailand is, the locals will be responsive to managers who exhibit feminine qualities such as, loyalty and understanding. However, this study also found that although Thais did have a more feminine than masculine orientation, they did not have a significantly higher need for achievement. It is possible that as the economy continues to develop and become increasingly global in Thailand, values are indeed changing.